2018
DOI: 10.1088/1361-6463/aac3e7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CF4 content on particle densities and reaction pathways in atmospheric-pressure Ar/CF4 pulsed dielectric barrier discharge plasma

Abstract: Ar/CF4 discharge plasma etching is a promising approach to achieving a high etch rate and anisotropic etching. A 1D fluid model is established to numerically study the effects of CF4 content on particle densities and reaction pathways in Ar/CF4 pulsed dielectric barrier discharge plasma at atmospheric pressure. The simulation results indicate that, with increasing CF4 content, Ar+ densities decrease but the densities of other positive ions increase, and the electron densities do not undergo a dramatic change b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Our results are consistent with Iwase's work [36]. Bai et al [13] reported that the concentration of CF + 4 is greater than that of CF + 3 because the Penning ionization reaction between inert gas and CF 4 were not considered in their simulation.…”
Section: He + 05% Cfsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with Iwase's work [36]. Bai et al [13] reported that the concentration of CF + 4 is greater than that of CF + 3 because the Penning ionization reaction between inert gas and CF 4 were not considered in their simulation.…”
Section: He + 05% Cfsupporting
confidence: 93%
“…However, when the content of fluorine groups were low, the holdoff voltage decreased. Bai et al [13] pointed out that the inhibitor precursor F-containing species played important roles in anisotropic etching. However, due to the extremely low sticking probability, CF 3 had no evident influence on the forming of the protective layer due to its extremely low sticking probability [14].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional DBD excited by alternating current power supply, the nanosecond pulsed DBD (called NPDBD) effectively generates more stable, homogenous and highly chemical activity non-equilibrium discharge plasma. [15][16][17][18][19][20][21] Khalifeh et al have experimentally studied extra pure H 2 production through CH 4 decomposition using the NPDBD plasma and Pt-Re catalyst. 22 Zhang et al have researched temporal evolution characteristics and chemical kinetics of the non-oxidative CH 4 conversion in the well-designed repetitively NPDBD plasma reactor.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation model consists of the homemade one-dimensional plasma model and the two-dimensional combustion model based on software CHEMKIN-PRO. In previous studies, the plasma model has been implemented and validated for various NPDBD plasmas in different gas compositions. Figure shows the schematic of the NPDBD plasma-assisted combustion system used in this work. The descriptions of the NPDBD plasma model and the planar shear flow combustion model are presented in Sections and 4.2, respectively.…”
Section: Methodsmentioning
confidence: 99%